Akibat Hukum Suatu Peralihan Hak Atas Tanah Yang Didasarkan Pada Unsur Penyalahgunaan Keadaan Dan Pembayaran Fiktif (Studi Putusan Mahkamah Agung Nomor 523 K/Pdt/2017) - Amanda Amri Hasibuan (Ilmu Hukum Prima (IHP), 2021)
Land title transfer often shows vitiated consent caused by defraud, coercion, and error, but it cannot be denied that vitiated consent occurs when one of the parties has suffered big financial loss so that he has to agree on it. It can occur when one of them is more superior than the other one, either economical or psychological so that he will use it to get the consent on the clauses in the contract. In this case, he is considered as having committed abuse of circumstances.The research problems are how about the regulation in land title transfer as it he research used juridical normative method with descriptive analytic approach. The data were obtained from primary, secondary, and tertiary legal materials. They were gathered by conducting library research and understanding the Jakarta Selatan District Court’s Verdict No. 305/Pdt.G/2014/PN.Jkt.Sel, the Appeal No. 215/Pdt/2016/PT.DKI, and Cassation Appeal No. 523 K/Pdt/20017 concerning the abuse of circumstances. They were analyzed systematically, and the conclusion was drawn deductively.Based on the research on land title transfer, it is recommended that all of the legal acts or juristic facts be included in authentic deeds made before Notaries/PPATs and registered in the Land Office to have them validated. Legal consequence the absence of fair right and obligation will cause lawsuits. The Jakarta Selatan District Court’s Verdict No. 305/Pdt.G/2014/PN.Jkt.Sel states that the Defendant I has committed illegal act by abusing circumstances and fictitious payment on the disputed object, and, therefore, all issued deeds as revoked.